Drugs and our world - Super, Gretchen, 1955- (Frederick, Md. : Twenty-First Century Books, 1990)
Describes, in simple terms, the harmful psychological and physical effects of drug usage and outlines reasons for not using drugs.
Includes index.
Keywords: Drug abuse -- Juvenile literature; Drug abuse -- United States -- Juvenile literature; Drug abuse